“Isobel Rainey. EFL in the Secondary School Sector: Grassroots Teachers’ Realities and Practices”: Review of the Book - Дроботун, Вікторія; Кавицька, Тамара (Київський національний університет імені Тараса Шевченка, 2019)
The article is a review of the book “Isobel Rainey. EFL in the Secondary School Sector: Grassroots Teachers’ Realities and Practices”. An excellent resource for teachers, students and EFL enthusiasts, this book is an interesting research in the field of teaching English as a foreign language in a secondary education setting. The author discusses typical challenges faced by most secondary school teachers of English all over the world by inviting readers to an engaging professional dialogue on the issue that has not received much attention in literature. In her book, Isobel Rainey combines a broad theoretical analysis of the secondary school EFL research with observations of classroom activities, which breathes life into the author’s narrative. The description of teachers’ classroom experiences is the most valuable asset of the book, as it gives teachers practical tips on how to respond to certain challenges in the classroom. Another positive aspect of the book is that with the terminology explained, the writing is clear and understandable; it allows readers to easily follow the author’s narration, which makes the book attractive for language educators whose English is a second or foreign language.

Isobel Rainey. EFL in The Secondary School Sector: Grassroots teachers’ realities, research and practices. CreateSpace Independent Publishing Platform, 2017. – 310p.
“ISOBEL RAINEY. EFL IN THE SECONDARY SCHOOL SECTOR: GRASSROOTS TEACHERS’ REALITIES, RESEARH AND PRACTICES” : ОГЛЯД ПОСІБНИКА
Keywords: Grassroots teachers; secondary school sector; EFL; classroom observations.